Prevention of HIV-1 Transmission Through Breastfeeding: Efficacy and Safety of Maternal Antiretroviral Therapy Versus Infant Nevirapine Prophylaxis for Duration of Breastfeeding in HIV-1-Infected Women With High CD4 Cell Count (IMPAACT PROMISE). (1st April 2018) - Flynn, Patricia M.; Taha, Taha E.; Cababasay, Mae; Fowler, Mary Glenn; Mofenson, Lynne M.; Owor, Maxensia; Fiscus, Susan; Stranix-Chibanda, Lynda; Coutsoudis, Anna; Gnanashanmugam, Devasena; Chakhtoura, Nahida; McCarthy, Katie; et al.
Abstract : Background: No randomized trial has directly compared the efficacy of prolonged infant antiretroviral prophylaxis versus maternal antiretroviral therapy (mART) for prevention of mother-to-child transmission throughout the breastfeeding period. Setting: Fourteen sites in Sub-Saharan Africa and India. Methods: A randomized, open-label strategy trial was conducted in HIV-1–infected women with CD4 counts ≥350 cells/mm 3 (or ≥country-specific ART threshold if higher) and their breastfeeding HIV-1–uninfected newborns. Randomization at 6–14 days postpartum was to mART or infant nevirapine (iNVP) prophylaxis continued until 18 months after delivery or breastfeeding cessation, infant HIV-1 infection, or toxicity, whichever occurred first. The primary efficacy outcome was confirmed infant HIV-1 infection. Efficacy analyses included all randomized mother–infant pairs except those with infant HIV-1 infection at entry. Results: Between June 2011 and October 2014, 2431 mother–infant pairs were enrolled; 97% of women were World Health Organization Clinical Stage I, median screening CD4 count 686 cells/mm 3 . Median infant gestational age/birth weight was 39 weeks/2.9 kilograms. Seven of 1219 (0.57%) and 7 of 1211 (0.58%) analyzed infants in the mART and iNVP arms, respectively, were HIV-infected (hazard ratio 1.0, 96% repeated confidence interval 0.3–3.1); infant HIV-free survival was high (97.1%, mART and 97.7%, iNVP, at 24 months). There were no significant differences between arms in median time to breastfeeding cessation (16 months) or incidence of severe, life-threatening, or fatal adverse events for mothers or infants (14 and 42 per 100 person-years, respectively). Conclusions: Both mART and iNVP prophylaxis strategies were safe and associated with very low breastfeeding HIV-1 transmission and high infant HIV-1–free survival at 24 months. Abstract : Supplemental Digital Content is Available in the Text.